PERHITUNGAN PAJAK PENGHASILAN BADAN TERUTANG CV RUMAH SAFETY KABUPATEN BANJAR TAHUN 2024 - Nada Ermaya Sofie; Saprudin; Norlena (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
The purpose of this study is to determine the calculation of corporate income tax payable that has been applied by CV Rumah Safety Kabupaten Banjar and what should be done. Aspects included in the scope of this study are commercial accounting and fiscal accounting owned by the Company, the type of data used in this study is quantitative data, Research data is analyzed descriptively, there are 4 (four) stages or in the components of analyzing data, namely data collection, data reduction, data presentation, and conclusions. The results of the study show a difference in commercial profit of Rp 610,394,856.75. This is because fiscal reconciliation is carried out so that it changes the profit value in the income statement according to fiscal. The difference in corporate income tax payable is Rp 183,231,626.50. The difference in the value of corporate income tax between the company and the research results in the emergence of a corporate income tax value that must still be paid by the Company. Based on the research findings, CV Rumah Safety, Banjar Regency, must pay closer attention to Tax Law Number 36 of 2008, particularly Article 9, which regulates costs that may not be included in financial reports to reduce a company's gross income. This allows CV Rumah Safety, Banjar Regency, Banjarmasin, to correctly apply the law for calculating corporate income tax payable in accordance with current regulations.